2017
DOI: 10.17576/mjas-2017-2104-26
|View full text |Cite
|
Sign up to set email alerts
|

Alchemilla vulgaris AND Filipendula ulmaria EXTRACTS AS POTENTIAL NATURAL PRESERVATIVES IN BEEF PATTIES

Abstract: Alchemilla vulgaris (AV) and Filipendula ulmaria (FU) are European medicinal plants possess bioactive compounds that exhibit many pharmacological benefits in human. The present work aims to assess two plants ethanolic extract; AV and FU of their antioxidant activities as natural preservative in beef patties. All plant samples were analysed using total polyphenol content (TPC), their antioxidant activities using Trolox Equivalent Antioxidant Capacity (TEAC), Ferric Reducing Antioxidant Power (FRAP), color and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The antioxidant activity measured with TEAC was 68.21 mmol of Trolox (TE)/g of dry weight (DW). Whereas FRAP assay was 40.12 mmol of TE/g DW [ 59 ].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…The antioxidant activity measured with TEAC was 68.21 mmol of Trolox (TE)/g of dry weight (DW). Whereas FRAP assay was 40.12 mmol of TE/g DW [ 59 ].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…A previous study showed that the most commonly used natural antioxidant in diets of ruminants and monogastric animals is Tp. High concentrations of Tp in the cellular membranes results in neutralization of the unstable free radicals produced during storage [26]. The role of Tp is to generate stable molecules that do not degrade once oxidized.…”
Section: Lipid Degradation Measurements On Meat Patties Wrapped With ...mentioning
confidence: 99%